El orador-cisne: Luciano, la retórica y los rétores - Karavas, Orestis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
Lucian of Samosata, the satirical author of the second century AD, is known especially for his four collections of short dialogues (those of the Gods, the Dead, the Courtesans and the Sea-gods). However, he produced a large and varied oeuvre, which can be studied from different angles. The present paper is about Lucian’s attitude towards rhetoric and rhetors, under five points of vue: i) the reference of Lucian to the attic orators, ii) the quoted rhetorical texts, iii) some lucianic works written in rhetorical style, iv) the tribunal scenes in Lucian and v) the role of the personnification of Rhetoric in them.
Keywords: Lucian; Rhetoric; Orator